Analysis of stochastic automata algorithm for relaxation labelling - Sastry, P.S.; Thathachar, M.A.L. (IEEE transactions on pattern analysis and machine intelligence, 1994)
A parallel stochastic algorithm for relaxation labeling is analyzed. For the case of symmetric compatibility functions, it is proved that time algorithm will always converge to a consistent labeling.< >